2008
DOI: 10.2741/3018
|View full text |Cite
|
Sign up to set email alerts
|

Cdt1 and Geminin in cancer: markers or triggers of malignant transformation?

Abstract: Cdt1 and its inhibitor Geminin are important regulators of replication licensing. In normal cells, a critical balance between these two proteins ensures that firing of each origin along the genome will take place only once per cell cycle. Cdt1 overexpression in cell lines and animals leads to aberrant replication, activates DNA damage checkpoints and predisposes for malignant transformation. Geminin inactivation mimics the effects of Cdt1 overexpression in cells and generates mitotic defects and abnormal chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 65 publications
4
55
0
3
Order By: Relevance
“…For example, the combination of an in vivo licensing assay with depletion or overexpression of specific factors may allow the identification of novel factors that block or enhance DNA licensing. Moreover, given that Cdt1/Cdc6 overexpression and, thus, overlicensing of DNA has been associated with malignant transformation and tumorigenesis, the licensing system has been proposed as a novel molecular target for anticancer drug design (23,25). An in vivo licensing assay may offer a new approach for cell-based screens for the identification and validation of antitumor compounds and drugs under development that will block DNA licensing and, thus, DNA replication in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the combination of an in vivo licensing assay with depletion or overexpression of specific factors may allow the identification of novel factors that block or enhance DNA licensing. Moreover, given that Cdt1/Cdc6 overexpression and, thus, overlicensing of DNA has been associated with malignant transformation and tumorigenesis, the licensing system has been proposed as a novel molecular target for anticancer drug design (23,25). An in vivo licensing assay may offer a new approach for cell-based screens for the identification and validation of antitumor compounds and drugs under development that will block DNA licensing and, thus, DNA replication in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and extent of MCM loading onto chromatin must be accurately controlled through the cell cycle and coordinated with S phase onset. Both underlicensing and overlicensing have been linked to DNA replication stress, genomic instability, and malignant transformation (23)(24)(25).…”
mentioning
confidence: 99%
“…However, it is well known in other eukaryotes and more specifically in human cells that altered regulation of DNA replication licensing due to changes in CDT1 activity results in aberrant replication, activates DNA damage checkpoints and predisposes for malignant transformation (Petropoulou et al, 2008). Therefore, regulation of pre-RC activity is likely to be crucial for the maintenance of genome integrity also in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, CDT1 activity is precisely controlled by its negative regulator Geminin, which ensures the firing of each replication origin to occur once per cell cycle. CDT1 accumulation, as a result of RBX1 silencing, would disrupt this fine balance, thus causing aberrant replication to trigger DNA damage checkpoints (52). Indeed, a recent study showed that CDT-1 overexpression in human cancer cells causes DSB to trigger DDR (31), whereas overexpression of Double-arked (Dup), the Drosophila ortholog of CDT1, causes DNA re-replication and DNA damage (53).…”
Section: Rbx-1 Silencing Induces Ddr and Lethal Phenotypes In C Elegmentioning
confidence: 99%